STRATEGI MENINGKATKAN MUTU PENDIDIKAN MELALUI MANAJEMEN SARANA DAN PRASARANA PADA SMK NEGERI 1 SINGKAWANG - Mellky Yulius (Universitas Muhammadiyah Purwokerto, 2020)
ABSTRACT The school is a social institution whose existence is part of the nation's social system which aims to produce capable, democratic, responsible, faithful, faithful, physically and spiritually healthy individuals, possessing knowledge and skills, having a steady and independent personality. In order to achieve these objectives a strong curriculum is needed, both infrastructure and superstructure. The research aims to reveal strategies to improve the quality of education through the management of facilities and infrastructure in Singkawang 1 Vocational High School (SMK) with a focus on: 1). Facilities and infrastructure planning in Singkawang State Vocational School 1, 2). Utilization of facilities and infrastructure in State Vocational School 1 Singkawang, 3). Monitoring of Facilities and Infrastructure at SMK Negeri 1 Singkawang, 4). Reporting on facilities and infrastructure at SMK Negeri 1 Singkawang, 5). Obstacles encountered in facilities and infrastructure at SMK Negeri 1 Singkawang. The research method used is descriptive research with a qualitative approach. Data validity is done by data triangulation, technical triagulation and member checking. Then the interactive data analysis with data reduction, data presentation, conclusion or verification. The results showed that: 1). facility and infrastructure program planning has been made by the student department to develop facilities in school activities. 2). The use of facilities and infrastructure is implemented in accordance with the learning needs of each teacher and regulated and monitored in an orderly manner, 3). Supervision of facilities and infrastructure has been done directly by the school principal, 4). Reporting has been carried out regularly by the vice-principal on student affairs to the principal, 5). Constraints faced in facilities and infrastructure are financing both for procurement and maintenance. Based on the results of the study suggested the following things: 1) The principal is expected to optimize supervision of all activities that have been planned so that the specified goals can be achieved. 2) Need to involve the community in the procurement of financing and maintenance of facilities and infrastructure. 3) Teachers, administration is expected to be involved in the management of facilities and infrastructure. Keywords: Strategy, Education Quality, Management of Facilities and Infrastructure.